Policy Constraints and the Recovery from Banking Crises - Christian Ambrosius (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
While much research has been done on causes and effects of banking crises, little is know about what determines recovery from banking crises, despite of large variations in post-crises performances across countries. In order to identify factors that determine the length of recovery (e.g. the time it takes until countries reach their pre-crisis level of per capita GDP), this paper employs event history analysis on 138 incidents of banking crises between 1970 and 2013. Cox Proportional Hazards show that both domestic and external constraints play a key role for recovering from banking crises. In particular, countries that suffered from simultaneous currency crises as well as those with overvalued currencies tended to recover later. Regarding external factors, a low growth of world trade has a negative effect on recovery, and so does uncertainty in financial markets as reflected in high gold prices. Moreover, contractionary monetary policy of the US Fed as Central Bank of the international key currency has a negative effect on the length of recovery in emerging markets and developing countries with open capital accounts. The latter empirical relationship reflects the vulnerability of developing countries and emerging markets to policies in the global financial centers and points to the necessity of understanding crises policies as embedded within monetary asymmetries that significantly limit the policy space of countries at the lower ends of the global currency hierarchy.
Keywords: E44; H12; O23; 330